The Role of the Tourism Sector on Employment Opportunities in Indonesia - Sarwoko, Sarwoko (Universitas Muhammdaiyah Surakarta, 2014)
The objective of this paper are to examine the long run effects of tourism receipt and national real product domestic bruto on the employment in Indonesia and the causality relationship among those variables in a multivariate model using annual data spanning 1980-2011. To test the unit root, we employed ADF and PP tests. To test cointegration we used Johansen dan Joselius model (1990) and to test the direction of the causality relationship we used Ngranger causality with VECM or Wald Block Exogeneity test. The empirical findings show that the long run equilibrium exists among those variabels and there are unsensitive elasticities between tourism receipt and national real product domestic bruto on the employment. National real product domestic brutto had Ngranger causality on the employment with bidirectional causality, while tourism receipt had Ngranger causality on employment with unidirectional causality.